Improving the Management Efficiency of Enterprises in the Electric Power Sector - Shakhrukh, Samiev (Journal of Learning on History and Social Sciences, 2024)
This scientific article examines the reforms carried out to improve the management efficiency of enterprises in the electric power sector and their results, existing problems in the network, problems in the regulation and management of the electric power sector and gives suggestions and recommendations on ways to eliminate them.